Evaluation of sheep exposure to poly- and perfluoroalkyl substances through hair sample analysis - Gonkowski Sławomir; Martín Julia; Kadyralieva Nariste; Aparicio Irene; Santos Juan Luis; Alonso Esteban (Journal of Veterinary Research, 2025)
Poly- and perfluoroalkyl substances (PFASs) are a numerous group of synthetic organic compounds used in various industries. They pollute the natural environment and negatively affect humans and animals. The aim of the present investigation was to assess the exposure of sheep bred in the Kyrgyz Republic to six selected PFASs.